You are given an integer array nums and an integer target.
You want to build an expression out of nums by adding one of the symbols '+' and '-' before each integer in nums and then concatenate all the integers.
For example, if nums = [2, 1], you can add a '+' before 2 and a '-' before 1 and concatenate them to build the expression "+2-1".
Return the number of different expressions that you can build, which evaluates to target.
Example 1:
Input: nums = [1,1,1,1,1], target = 3
Output: 5
Explanation: There are 5 ways to assign symbols to make the sum of nums be target 3.
-1 + 1 + 1 + 1 + 1 = 3
+1 - 1 + 1 + 1 + 1 = 3
+1 + 1 - 1 + 1 + 1 = 3
+1 + 1 + 1 - 1 + 1 = 3
+1 + 1 + 1 + 1 - 1 = 3
Example 2:
Input: nums = [1], target = 1
Output: 1
Constraints:
1 <= nums.length <= 20
0 <= nums[i] <= 1000
0 <= sum(nums[i]) <= 1000
-1000 <= target <= 1000
Solutions
Solution 1: Dynamic Programming
Let's denote the sum of all elements in the array \(\textit{nums}\) as \(s\), and the sum of elements to which we assign a negative sign as \(x\). Therefore, the sum of elements with a positive sign is \(s - x\). We have:
\[
(s - x) - x = \textit{target} \Rightarrow x = \frac{s - \textit{target}}{2}
\]
Since \(x \geq 0\) and \(x\) must be an integer, it follows that \(s \geq \textit{target}\) and \(s - \textit{target}\) must be even. If these two conditions are not met, we directly return \(0\).
Next, we can transform the problem into: selecting several elements from the array \(\textit{nums}\) such that the sum of these elements equals \(\frac{s - \textit{target}}{2}\). We are asked how many ways there are to make such a selection.
We can use dynamic programming to solve this problem. Define \(f[i][j]\) as the number of ways to select several elements from the first \(i\) elements of the array \(\textit{nums}\) such that the sum of these elements equals \(j\).
For \(\textit{nums}[i - 1]\), we have two choices: to select or not to select. If we do not select \(\textit{nums}[i - 1]\), then \(f[i][j] = f[i - 1][j]\); if we do select \(\textit{nums}[i - 1]\), then \(f[i][j] = f[i - 1][j - \textit{nums}[i - 1]]\). Therefore, the state transition equation is:
We can observe that in the state transition equation of Solution 1, the value of \(f[i][j]\) is only related to \(f[i - 1][j]\) and \(f[i - 1][j - \textit{nums}[i - 1]]\). Therefore, we can eliminate the first dimension of the space and use only a one-dimensional array.
The time complexity is \(O(m \times n)\), and the space complexity is \(O(n)\).